Tren Wisata Dalam Pengembangan Wisata Halal Berbasis Budaya Museum La Galigo Dalam Preferensi Generasi Z - M. Nur; Tria Aini Andara; Dian Malinda (CV. Kurnia Grup, 2026)
The development of the tourism sector has encouraged the emergence of tourism concepts that emphasize not only recreation but also cultural values, educational experiences, and the needs of Muslim travelers. Museum La Galigo in Makassar has significant potential to be developed as a culture-based halal tourism destination; however, it has not yet fully attracted the interest of Generation Z. This study aims to analyze tourism trends influencing the development of culture-based halal tourism, identify Generation Z's preferences, and examine the role of digital media and halal facilities in increasing visitors' interest. The research employed a qualitative method with a descriptive approach using observation, interviews, documentation, and literature review. The findings indicate that Generation Z is more interested in destinations that offer educational experiences, historical value, and engaging digital promotion. In addition, the availability of halal facilities enhances the comfort of Muslim visitors. Therefore, the development of Museum La Galigo should be supported through service innovation, optimized digital promotion, and adequate halal facilities to strengthen its attractiveness as a cultural tourism destination for Generation Z.